Public theology: : A word of the Church in pluralistic societies - Villagrán Medina, Gonzalo (Razón y fe, 2022)
Peter Berger, a privileged interpreter of the sociology of religion today, affirmed that the ultimate key to understanding the social reality in which we live is pluralism, which encompasses the secularization that is most immediate to us. The current moral and religious pluralism of societies forces us to seek new paradigms for the public discourse of the Church. Since the eighties of the last century, there has been a response to this challenge in the theological tradition of the Church: public theology. This school of thought is determined by the basically hermeneutical foundations of David Tracy and has been successfully applied by moralists such as David Hollenbach. It can be a very valuable inspiration for thinking about the word and action of the Church in our pluralistic societies at all levels.
Keywords: secularization; pluralism; natural law; public theology; analogical imagination; critical correlation; hermeneutics